Case Study of Risk Factors Caused Paranoid Type Schizophrenia Disorder - Inocencia Vivinca Arhadita; Nanda Audia Vrisaba (International Conference on Psychology and Education (ICPE), 2023)
Schizophrenia is a psychological disorder characterized by thought processes that are separated from reality, causing individuals to have a chaotic and frightening world. One type of schizophrenia that is often encountered in Indonesia is paranoid schizophrenia characterized by sufferers who often experience auditory hallucinations, visual hallucinations, various types of delusions or delusions accompanied by feelings of fear and anxiety. In the research method used is a case study with a qualitative approach. The assessment techniques used are participant observation or direct involvement in the subject's life during daycare rehabilitation, semi-structured interviews with patients and significant others (SO) and psychological tests (HTP, BAUM and DAM). The research subject is a male patient with the initials WH aged 37 years who has experienced history of relapes 8 times. The results showed that there were two factors causing the symptoms of schizophrenia in the subject, namely internal and external factors. The results of the study also analyzed the subject's psychological disorders based on Alfred Adler's parenting theory regarding being pampered or pampered which influenced the emergence of neurotic disorders in the subject. Based on the research, it can be explained that adherence to taking medication, supervision of the family environment and the institution is very influential on the subject's recovery during the treatment period.